Stakeholder Management in the Local Government Decision-Making Area: Evidences from a Triangulation Study with the English Local Government - Ricardo Corrêa Gomes (RAC - Revista de Administração Contemporânea, 2006)
The stakeholder theory has been in the management agenda for about thirty years and reservationsabout its acceptance as a comprehensive theory still remains. It was introduced as a managerial issueby the Labour Party in 1997 aiming to make public management more inclusive. This article aims tocontribute to the stakeholder theory adding descriptive issues to its theoretical basis. The findings arederived from an inductive investigation carried out with English Local Authorities, which will mostlikely be reproduced in other contexts. Data collection and analysis is based on a data triangulationmethod that involves case-studies, interviews of validation and analysis of documents. The investigationproposes a model for representing the nature of the relationships between stakeholders and thedecision-making process of such organizations. The decision-making of local government organizationsis in fact a stakeholder-based process in which stakeholders are empowered to exert influences due topower over and interest in the organization´s operations and outcomes